LINC-32. REPORT OF AN INITIAL SITE VISIT TO DETERMINE FEASIBILITY AND IMPLEMENTATION OF A COMPREHENSIVE NEURO-ONCOLOGY PROGRAM IN KENYA. (4th December 2020) - Armstrong, Beth; Mbiro, Mark; Magoha, Michael; Okemwa, Minda; Mwang'ombe, Nimrod; Coven, Scott
Abstract: BACKGROUND: Pediatric central nervous system (CNS) tumors are the leading solid tumors in the United States, but vastly under-reported in the African population. There's limited data on childhood brain tumors as well as the histopathological distribution in Kenya. This report surveys as an initial site visit to determine the feasibility of a comprehensive neuro-oncology program at Kenyatta National Hospital (KNH) in Nairobi, Kenya. DESIGN: This collaboration began with a visit from the director of neuropathology at KNH to our neuro-Oncology program at Riley Hospital for Children at Indiana University Health in May 2019. This report includes recommendations from the May 2019 trip, as well as a reciprocal site visit to Kenya in January 2020. RESULTS: Building off the May 2019 trip, a brain tumor registry has been initiated and maintained. Additionally, the KNH program has many necessary components to forming a comprehensive neuro-oncology program, including capable neurosurgeons with a neurosurgical training program, radiology, intensive care unit, oncology ward, rehab, skilled nursing, and radiation oncology services. Currently, neurosurgery, radiology, and pathology meet weekly to review challenging cases. CONCLUSION: Kenyatta National Hospital has the expertise to build a comprehensive neuro-oncology program. The program currently lacks a dedicated nurse coordinator and "specialist" in neuro-oncology. Ongoing discussions with local stakeholders are aimed to galvanize national support to improve awareness for children with brain tumors and to plan a multidisciplinary neuro-oncology symposium in 2021. In the meantime, telemedicine efforts can support nursing education and reiterate the multidisciplinary needs for children with brain tumors.